Correction: Biodegradable nanoparticles bearing amine groups as a strategy to alter surface features, biological identity and accumulation in a lung metastasis model. Issue 46 (6th November 2018) - Esposito, Diletta; Conte, Claudia; Poggetto, Giovanni Dal; Russo, Annapina; Barbieri, Antonio; Ungaro, Francesca; Arra, Claudio; Russo, Giulia; Laurienzo, Paola; Quaglia, Fabiana
Abstract : Correction for 'Biodegradable nanoparticles bearing amine groups as a strategy to alter surface features, biological identity and accumulation in a lung metastasis model' by Diletta Esposito et al., J. Mater. Chem. B, 2018, 6, 5922–5930.